Dangerous routes: insecurity and human mobility in Mexico - PARÍS-POMBO, María Dolores (Papeles de Población, 2018)
Every year, thousands of Guatemalan, Salvadoran and Honduran unauthorized migrants** travel through Mexico to reach the U.S. As the governments of these two countries intensify surveillance and multiply checkpoints, they force migrants to follow more dangerous routes to reach their destination. Migrants are exposed to multiple hazards caused by the lack of public safety, rising crime rate, and the corruption of Mexican authorities. This article analyzes the migratory routes, the means of transportation, and the evolution of human smuggling from Central America to the U.S. and the social risks confronted by migrants in Mexico.